Management Skills of Department Heads in Relation to Employees Work Performance (International Journal of Scientific Research and Management (IJSRM), 2023)
The management skills of department heads play a vital role in determining employees’ work performance. Department heads are expected to possess good qualities of manager and to deal effectively and efficiently require special skills which make the manager successful in their task. The department heads with high levels of management skills are also likely to have high levels of self-worth and self-esteem, which can impact every area of their lives, from relationships to employment and work performance. The study investigated the management skills of department heads in relations to employees’ work performance of permanent regular casual employees of Local Government Unit of Negros Occidental during the fiscal years 2020. The design of this research is a descriptive study using a questionnaire as the research instrument. A total of 225 permanent and casual employee were involved as respondents in this study. The variables considered were age, sex, and highest educational attainment. The findings showed that the department heads’ level of management skills is all at a very high level. The employees’ work performance level during the fiscal year 2020 was interpreted as very satisfactory based on their OPCRF. The findings also showed that there was no significant difference in the department heads’ level of management when grouped and compared according to sex and highest educational attainment. However, results showed a significant difference in variables age. A significant difference in the employees’ level of work performance when grouped and compared according to age and highest educational attainment, while sex showed no significant difference.Department Heads seem to be the most operational tool in influencing people, so they strive willingly and enthusiastically towards the accomplishment of goals in the department. Department heads design motivation systems to encourage employees to perform most effectively and draw potential candidates for promotion.